2023
DOI: 10.1177/02692163231164452
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of family members witnessing the diminishing drinking of a dying relative in hospital: A narrative inquiry

Abstract: Background: The optimal management of diminishing drinking at the end of life is contentious. Clinicians and family members may understand the phenomenon differently and hold divergent priorities regarding care. Family members can be distressed by diminishing drinking and its management, particularly when in a hospital environment. Aim: To explore the experiences of family members when witnessing the diminishing drinking of a dying relative. Design: A narrative inquiry methodology, derived from pragmatism. Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Still, yet other families become entrenched in fighting back against decline through trying to bolster nutritional intake by any means possible. 89 , 90 , 91 Research has yet to be conducted to discern if the severity of cachexia correlates with family member distress or family functioning.…”
Section: Contemporary Areas Of Interest and Future Research Directionsmentioning
confidence: 99%
“…Still, yet other families become entrenched in fighting back against decline through trying to bolster nutritional intake by any means possible. 89 , 90 , 91 Research has yet to be conducted to discern if the severity of cachexia correlates with family member distress or family functioning.…”
Section: Contemporary Areas Of Interest and Future Research Directionsmentioning
confidence: 99%
“…When patients are near the end of life, they may stop eating and drinking or diminish their drinking [11]. A review study found that most family members who experienced diminishing drinking by their dying relative were distressed by it [12].…”
Section: Introductionmentioning
confidence: 99%